Factors That Determine Satisfaction between Asian and Western Travelers Staying In Malaysian Hotels - Wang, Shi Ming (2012)
This paper aims to examine the factors that measure different satisfaction between the Asian and Western travelers during their stay in Malaysia. Meanwhile, it seeks to analyze the importance of the tangible and intangible factors in the hotel industry. The research questions are utilized to measure the differences between Asian and Western perception of hotel attributes. There are four dimensions (quality of services, value for money, atmosphere, and hotel image) in examining the relationship with customer satisfaction. Reliability analysis, factors analysis, mean analysis, independent T-Test and multiple regression analysis were used to examine the relationship between four dimensions and customer satisfaction. Moreover, the self-administration questionnaires were distributed to 200 travelers who were above 18 years old and had experience that staying in hotels in the past using convenience sampling method. In addition, the findings show that quality of services, value for money, atmosphere and hotel image have significant positive relationship with customer satisfaction for Asian travelers. At the same time, quality of services, value for money and atmosphere has significant positive relationship with customer satisfaction for Western travelers. Finally, recommendations are given to people who are interested in this topic and to future researchers.